THE TOXICITY OF SEEDS EXTRACT OF ANNONA SQUAMOSA L., LEAVES EXTRACT OF TERMINALIA CATAPPA L. AND LEAVES EXTRACT OF ACACIA NILOTICA L. ON THE MORTALITY OF AEDES AEGYPTI L. LARVAE - Dwi Wahyuni; Sandy Pradipta; Muhammad Ramadhan (UNEJ e-Proceeding, 2016)
Aedes aegypti L. is a species of mosquito that carries the dengue virus causes dengue fever. The way to solve the disease is still focused on synthesis larvacides which have a negative impact on the environment, it needs to be replaced with natural larvicides that are environmentally friendly. Annona squamosa L. seeds extract contains annonain and squomacin. Terminalia catappa L. leaf extract contains quinone, saponin, flavonoid and tannin. Acacia nilotica L. leaf extract contains terpenoid, saponin, flavonoid and tannin. This research aims to determine The toxicity of seeds extract of A. Squamosa, leaves extract of T. Catappa, and Leaves extract of A. nilotica on the mortality of Ae. aegypti. The method used in this research was complete randomized design using four replications. Concentration used 5, 10, 50, 100, 150, 200 and 250 ppm for the seeds extract of A. Squamosa, 50, 100, 150, 200, 250, 300 and 350 ppm for the leaf extract of T. catappa, and 80, 120, 180, 240, 300, 350 and 400 ppm for the leaf extract of A. nilotica. The data were analyzed using probit analysis to determine the LC50. The result showed LC50 is 109.43 ppm for A. Squamosa seeds extract, LC50 is 171.65 ppm for T. catappa and LC50 is 203.63 ppm for A. nilotica. This result showed the biggest toxicity is seeds extract of A. Squamosa.